Preregistration and registered reports. Issue 2 (3rd April 2021) - Reich, Justin
Abstract: Preregistration and registered reports are two promising open science practices for increasing transparency in the scientific process. In particular, they create transparency around one of the most consequential distinctions in research design: the data analytics decisions made before data collection and post-hoc decisions made afterwards. Preregistration involves publishing a time-stamped record of a study design before data collection or analysis. Registered reports are a publishing approach that facilitates the evaluation of research without regard for the direction or magnitude of findings. In this article, I evaluate opportunities and challenges for these open science methods, offer initial guidelines for their use, explore relevant tensions around new practices, and illustrate examples from educational psychology and social science.